HEAVY METAL CONTAMINATION IN WATER SOURCES IN POHUWATO REGENCY: IMPLICATIONS FOR BIODIVERSITY AND PUBLIC HEALTH IN GOLD MINING AREAS - Iyabu, Hendri; Baderan, Dewi Wahyuni K; Hamidun, Marini Susanti; Rahim, Sukirman; Rauf, Asda (Indonesian Biodiversity Journal, 2025)
Artisanal and small-scale gold mining (ASGM) can increase the levels of heavy metals in surface water and groundwater sources. This study was conducted to evaluate water quality in Pohuwato Regency, Gorontalo, Indonesia. Sampling was performed at three sites: a reservoir, an irrigation channel, and a well. The concentrations of lead (Pb), cadmium (Cd), iron (Fe), manganese (Mn), and mercury (Hg) were analyzed using Atomic Absorption Spectrophotometry (AAS). The results indicated that Hg concentrations ranged from 0.00883 to 0.01493 mg/L (≈8.8–14.9× above the WHO guideline value of 0.001 mg/L), Mn concentrations ranged from 0.1309 to 0.543 mg/L (≈1.3–5.4× above the WHO guideline value of 0.1 mg/L), while Pb concentrations ranged from 0.0019 to 0.0048 mg/L, Cd concentrations ranged from 0.0002 to 0.0006 mg/L, and Fe concentrations ranged from 0.0728 to 0.101 mg/L, all of which were below the recommended threshold values for drinking water. The findings emphasize the importance of mitigation strategies based on mining governance, strengthening water safety plans, as well as interventions for household water treatment (adsorption/filtration) and risk communication.